Recalcitrant crusaders? - Hailstone, Paula Z., author.
1 online resource (xiv, 235 pages).
Keywords: "This book explores the contribution of southern Italy and Sicily to the crusades and crusader states. By adopting the theme of identity as a tool of analysis, it argues that a far more nuanced picture emerges about the relationship than the dismissive portrayal by William of Tyre in his Chronicon, which has largely been accepted by later historians. Building upon previous scholarship in relation to Norman identity, it widens the discussion to evaluate the role of more fluid and evolving Italo-Norman and Italo-Sicilian identities, and how these shaped events. In so-doing, this book also argues that the relationship between the territories needs to be considered in different dimensions: direct involvement of leaders and rulers versus indirect engagement through the geography of southern Italy and Sicily. Over time, and as identities change, these two dimensions converge, making the kingdom itself a leading participant in crusading"--